Обзор нормативної бази по системі SMART GRID - Житник, М. В. (НТУ "ХПІ", 2016)
Пропонується розглянути систему smart grid, її історію виникнення та трансформацію до сучасного виглягу. Запропонована класифікація стандартів,яка відносяться до цієї системи для енергетичної галузі,розглянуті переваги при впровадженні,показники ефективності та оцінка ризиків. Також відображено,як поліпшити надійність за допомогою інтелектуальноі енергомережі. Зроблені висновки,що SMART GRID, надає можливості більш ефективного управління ресурсами енергосистеми і їх автоматизації, що дозволяє об’єднати мережеві функції і оптимізувати процеси експлуатації енергосистеми.

There have been proposed to watch how working smart grid stem,historical chronology and transformation in modern look. A smart grid is a modernized electrical grid that uses analog or digital information and communications technology to gather and act on information such as information about the behaviours of suppliers and consumers in an automated fashion to improve the efficiency, reliability, economics, and sustainability of the production and distribution of electricity.Electronic power conditioning and control of the production and distribution of electricity are important aspects of the smart grid. Roll-out of smart grid technology also implies a fundamental re-engineering of the electricity services industry, although typical usage of the term is focused on the technical infrastructure The smart grid represents the full suite of current and proposed responses to the challenges of electricity supply. In this article we can see classification standards,which belong to this system for the energy industry,shows advantages when used,index of efficiency and estimation of risks. Also shows how to improve reliability using smart grid. After come to the upshot, then this system gives to possibility of more effective management the resoursces of grid and their automation,optimize the processes of exploitation of grid.
Review of the regulatory framework for the system of smart grid
Keywords: автоматизована система управління; показник ефективності; надійність; оцінка ризиків; інтелектуальна енергомережа; automation control system; index of efficiency; reliability; estimation of risks; smart grid